(untitled) (Research, Society and Development, 2021)
Objective: To understand the perception of young university students about sexuality, and to describe the influencing factors of sexuality in the students’ conception. Method: A descriptive, qualitative study was conducted at a public university. Twenty-seven university students, of both genders, aged 18-29 years, participated. Three focus groups were conducted to discuss social, cultural aspects, sexual behavior and prevention of sexually transmitted infections. In the data analysis, the content analysis technique was used, emerging three categories. Results: Sexuality from the perspective of young people and factors influencing sexuality from the perspective of university students were categories with greater representativeness (54%). The concept of sexuality is related to self-recognition, physical attraction, desire and freedom of expression, and the influence of culture and religiosity on the sexuality of young people. Conclusion: Sexual behavior is influenced by cultural, social, religious, interpersonal and affective relationships, being modulated by the group of belonging of young people.